Prognostic and predictive factors for clinical and radiographic responses in patients with painful bone metastasis treated with magnetic resonance-guided focused ultrasound surgery. (1st January 2019) - Tsai, Yi-Chieh; Lee, Hsin-Lun; Kuo, Chia-Chun; Chen, Chun-You; Hsieh, Kevin Li-Chun; Wu, Meng-Huang; Wen, Yu-Ching; Yu, Hsiao-Wei; Hsu, Fang-Chi; Tsai, Jo-Ting; Chiou, Jeng-Fong
Abstract: Background: Magnetic resonance-guided focused ultrasound surgery (MRgFUS) is an alternative local therapy for patients with painful bone metastasis. However, little is known about the prognostic and predictive factors of MRgFUS in treating bone metastasis. Materials and methods: This retrospective study analyzed the performance status, treated site, pretreatment pain score, pretreatment tumor volume and lesion coverage volume factor (CVF) of 31 patients who underwent MRgFUS. A numerical rating scale for pain was used at the same time to assess the clinical response. Radiographic responses were evaluated using a modified version of The University of Texas MD Anderson Cancer Center criteria and reference to the MR imaging or computed tomography scans obtained 3 months after treatment. Univariate and multivariate logistic regression analyses were conducted to examine the effect of variables on clinical and radiographic responses. Results: The overall clinical response rate was 83.9% and radiographic response rate was 67.7%. Multivariate logistic regression analysis revealed that the better pretreatment Karnofsky performance status (KPS) (odds ratio: 1.220, 95% confidence interval (CI): 1.033–1.440; p = 0.019) was significantly associated with a more positive clinical response, and that the lesion CVF (odds ratio: 1.183, 95% CI: 1.029–1.183; p = 0.0055) was an independent prognostic factor for radiographic responses. The radiographic response of patients with lesion CVF ≥70% and CVF <70% were 91.7% and 52.6%, respectively ( p = 0.0235). Conclusion: The pretreatment KPS was an independent prognostic factor for clinical responses, and lesion CVF was an independent prognostic factor for radiographic responses.